PEMANFAATAN APLIKASI GOOGLE DOCS SEBAGAI PERANGKAT PENDUKUNG KEGIATAN BELAJAR MENGAJAR BAGI SISWA SMA AL-KAUTSAR PARUNGPANJANG - Hutagalung, Deanna Durbin; Megasari, Dian; Ridwan, Agus Septima (KOMMAS: Jurnal Pengabdian Kepada Masyarakat, 2025)
The development of learning media, teachers and students are required to be more creative in processing data and documents. Documents are one of the main components such as school regulation documents, teacher data, school administration, learning materials, exam questions and others. One source of learning for students at school in obtaining messages given by teachers is through learning media. One application that supports learning media is the Google Docs word processing application. The purpose of this activity is to provide training in the use of Google Docs as a learning medium for students of Al-Kautsar Parungpanjang High School. The method used is socialization and training in the use of Google Docs. Through this PKM activity, Al-Kautsar High School students have been able to document personal files well, and have begun to practice collaborating with friends in completing several important tasks.